HEGEMONIC MASCULINITIES AND SEXUAL AND REPRODUCTIVE HEALTH IN SAN SALVADOR DE JUJUY - Sona Sombory, Federico Matias (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2018)
This is an advance of an ongoing research, whose objective is to analyze the processes of socialization and social construction linked to hegemonic masculinity, between adult heterosexual men, in San Salvador de Jujuy and its incidence on sexual and reproductive health. This time I will analyze the particular forms in which that hegemonic masculinity expresses itself, with its ideal of strong and resistant body. This demands, in turn, risky behaviors that affect physical integrity and influence sexual practices and the care / self-care of health, in general, and sexual and reproductive health, in particular. For this, I will focus in part on the results obtained in the course of ethnographic surveys in three different areas of masculine homosociality: the “The Two Chinese” coffee shop, a basketball court and a group of heterosexual men who meet to play role and boards games, in different locations. It is in these places where distinctions are expressed around the masculine capitals put into play, age groups and socioeconomic compositions: I will pay special attention to the age range of the groups observed since it will allow me to show continuities and discontinuities with respect to the notions and practices on they should be male, sexual behaviors and sexual and reproductive health care, over time.